Nalar Keilmuan Bahasa Arab dalam Studi Ilmu-Ilmu Keislaman: Perspektif Kritik Nalar Arab Muhammad Abid Al-Jabiri - Rusydi, Muhammad (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2020)
The study of Islamic sciences cannot be separated from the text in which in this process Arabic plays a very strategic role. The Arab reasoning criticism of Muhammad Abid al-Jabiri, which was built on bayani, burhani, and irfani, needs to be accelerated in supporting the transformation of the study of Islamic sciences through the transformation of text to reason which then leads to an intuitive dimension. This can be done optimally if there is an effort to synergize the immanent linguistic structure in Arabic both from a phonological, morphological, syntactic or semantic perspective with a scientific structure that is immanent to the existing Islamic sciences.